PKM Product Innovation White AC Sweet Potato Becomes Chips and Cupcake in Sukodono - Suhartinah Suhartinah; Dewi Lusiana (OJS Universitas Muhammadiyah Gresik, 2019)
Most of the livelihoods of Sukodono Village’s people, Pujer District, Bondowoso Regency are farming; various kinds of agricultural products produced by the residents of Sukodono Village are white AC sweet potato. But, the yield of many white AC sweet potatoes which is not sold well causes decays and makes farmers give up. When I was a field supervisor of KKN Unmuh Jember, the KKN students and I promoted the Nafiah Posdaya which had once been formed. With the hope to overcome the problem of the white AC sweet potato farmers, namely by processing white AC sweet potato into chips and cupcakes manually. Because of the limited manual equipment, the white AC sweet potato used for the basic ingredients of chips and cupcakes is still in small quantities. Also, chips which are produced manually are not crunchy; contain lots of oil, long time production process and small amount of production. To overcome this, product innovation needs to be done by making white ac sweet potato chips with vacuum frying and spinner technology as well as making white ac sweet potato cupcakes with an electric mixer to mix dough and oven it. The problem is those partners do not have the knowledge, skills and capital to develop and be innovation product white ac sweet potato. There are four main activities in the Community Partnership Program dedication activities that are carried out by providing material training and practicing (1) implementing vacuum frying and spinner machines to make white AC sweet potato chips (2) packing with beautiful package (3) making cupcake with basic ingredients from white AC sweet potato (4) marketing model based on E-commerce Web-based Information Technology. The results of this training are crispy white AC sweet potato chips with a distinctive sweet potato taste because the slices are thicker than the other chips and delicious white ac sweet potato cupcake with attractive toping is a promising market opportunity. It is expected that the Community Partnership Program activities can improve the welfare of partners.